2021
DOI: 10.1136/bcr-2021-243824
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative postinfarct ventricular septal rupture during coronary bypass grafting

Abstract: We report a case of a ventricular septal rupture (VSR) which occurred during coronary artery bypass grafting (CABG) operation. The procedure took place 5 days after ST-elevation myocardial infarction of the inferior wall. The VSR repair was not performed at the time of the CABG operation. The intention was to wait until scar formation occurs to facilitate the repair. The patient was supported with venoarterial extracorporeal membranous oxygenation (VA-ECMO) and additional intra-aortic balloon pump (IABP) on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“… 16 , 17 , 18 Exemplifying this fact, we were surprised to encounter a similar case report by Kok et al published in 2021. 19 The authors similarly describe a case of VSR during a CABG operation, in which the patient was managed with ECMO cannulation and delayed surgical repair. Despite the variation in management between these two cases, this phenomenon of intraoperative VSR had not been described in the literature prior to 2021, and may reflect a rising rate of mechanical complications of MI due to delayed patient presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 17 , 18 Exemplifying this fact, we were surprised to encounter a similar case report by Kok et al published in 2021. 19 The authors similarly describe a case of VSR during a CABG operation, in which the patient was managed with ECMO cannulation and delayed surgical repair. Despite the variation in management between these two cases, this phenomenon of intraoperative VSR had not been described in the literature prior to 2021, and may reflect a rising rate of mechanical complications of MI due to delayed patient presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, multiple studies have demonstrated a longer time from symptom onset to first medical contact in the setting of MI during the COVID‐19 pandemic 16–18 . Exemplifying this fact, we were surprised to encounter a similar case report by Kok et al published in 2021 19 . The authors similarly describe a case of VSR during a CABG operation, in which the patient was managed with ECMO cannulation and delayed surgical repair.…”
Section: Discussionmentioning
confidence: 99%